Adaptive Leadership of Madrasah Principals in Sustaining the Quality Culture of Private Islamic Senior High Schools in Deli Serdang Regency - Wuri Tamtama Abdi; Umi Kalsum; Riswan Hadi; Suzatmiko Wijaya (Continuous Education: Journal of Science and Research, 2026)
Private Madrasah Aliyah must maintain educational quality while working with unequal resources, varied community expectations, and strong dependence on foundations. This study examines how adaptive leadership by madrasah principals sustains quality culture in four private Madrasah Aliyah in Deli Serdang Regency. It aims to explain how principals interpret institutional change, prioritize limited resources, distribute leadership, maintain learning routines, and manage stakeholder relations. The study used a qualitative multisite case study. Data came from semi-structured interviews, observations, and document analysis involving principals, vice principals, teachers, administrative staff, foundation or committee representatives, and students. The data were processed through transcription, coding, cross-site comparison, and reflexive thematic analysis, with triangulation, member checking, reflective notes, and an audit trail supporting trustworthiness. The findings identify five connected mechanisms: contextual reading of change, negotiation of quality priorities under resource constraints, distribution of responsibilities to internal actors, maintenance of quality through recurring academic and student-development routines, and reinforcement of external relations with foundations, parents, committees, alumni, and communities. Quality culture differed across sites, appearing through pesantren values, administrative order, discipline, or teacher-student closeness. The study concludes that adaptive leadership sustains quality culture through contextual coordination rather than formal control alone. The findings imply that principal development should strengthen diagnostic, collaborative, negotiation, and stakeholder-management skills alongside administrative competence.